Implementation of Early Breastfeeding Initiation and Bounding Attachment for Postpartum Mothers at Halilulik Hospital In 2021: A Qualitative Study - Flora Naibaho (Science Midwifery, 2022)
Breastfeeding is a knowledge that has existed for a long time and has an important role in maintaining human life (Astuti, 2013). Babies really need BA This situation is very important for babies to be able to adapt to their new environment. This research is operational research with a qualitative approach. This research will provide an analysis of matters relating to the implementation of IMD and BA in pregnant women at HALILULIK RSKM by using a systems approach. The place for this implementation analysis research is at the Halilulik RSKM. This research activity will be carried out in August September 2021. The subjects for this study were pregnant women (Bumil), health workers in the Midwifery Unit, namely doctors in charge, heads of rooms, midwives and nurses. HALILULIK RSKM did not find any problems in planning, organizing, controlling while for implementation problems were found because they were related to BPJS. Collaboration is needed between health institutions, especially related hospitals, to include the importance of implementing IMD and BA as hospital activity programs and policies for maternal health and especially for the growth and development of babies.